Report : proposed new interior design of Gobal Halal Support Centre (GHSC) for Halal Industry Development Corporation (HOC) at G .0 2 ,1 First Avenue Tower, Dataran Bandar Utama, Bandar Utama, 47300 Petaling Jaya, Selangor / Faredhun Md Sabis - Md Sabis, Faredhun (Faculty of Architecture, Planning and Surveying, 2011)
A final student in Diploma of Interior Architecture are required to come out with project report The report will summaries the student understanding of Design Process such as introduction to the project, site and building analysis, design proposal and finally the final schematic presentation The final project is proposed new interior design of Global Halal Support Centre(GHSC) for Halal Industry Developement Gorporation(HDC) at G.02, 1 First Avenue Tower, Persiaran Bandar Utama, Bandar Utama, 47800 Petaling Jaya, Selangor. Halal Industry Developement Corporation (HDC) is a research and development corporation. Where the corporation makes a reseach and collect data about Halal ussue through Islam arid biology(seience) point of view. It is also the central that develope, manage, distributes government funding and also promotes the local halal industries products to the world The Prime Minister of Malaysia have expressed and declared his vision that Malaysia should lead the charge in the global halal industry and that halal would be the new source of economic growth for the country. In order to translate this vision, HDC will launch a One Stop Centre Known as Global Halal Support Centre (GHSC). This is an important milestone to represent Malaysia commitment for supporting the industry and public at large. Based on the vision of HDC and also GHSC, student desided to take a chance to use it as a final project through HDC needs and requirement, in order to complete the project, student need to fimiliat se the stages starting with project brief. The finding of the research will have a good impact fo the students final project. Student will be able to investigate the organization structure in order to come out wth condusive space planning. The finding also will benefits the student knowledge interm of finding the right corporate scheme and identity of the company.